Fall risk in older adults hospitalized with tumours: Contributing factors and prediction model - Xiaoyan Liu; Chen Dong; Rui Zhao; Zhifeng Gu; Chi Sun (Wiley, 2023)
Abstract Aim Rates vary widely across hospitals globally and typically range from 3 to 11 falls per 1000 bed days and as 7-11 in Affiliated Hospital of Nantong University. This study determined to explore contributing factors and poor prognosis of fall in elderly tumour patients in China. Design A cross‐sectional study. Methods 161 older adults were invited to participate in this study and completed a self‐reported questionnaire, took blood tests, and received the exam of musculoskeletal ultrasound. Results Among 161 patients, falls occurred in 41 cases, accounting for 24.8%. 51.6% of older adults suffered from intermediate‐to‐high risk of falls. Fall history, reduced self‐care ability, sleep disturbance, hearing impairment, hyperkyphosis, chronic disease, platelet count, and the thickness of left muscle rectus femoris (LF‐MLT), and left cross‐sectional area (LF‐CSA) were all contributing factors of fall, and higher risk of fall indicating lower quality of life. A fall prediction model was established in this study based on above contributing factors with good prediction efficiency (AUC = 0.920). Patient or public contribution The patient volunteers participated in this study and provided valuable data for the final analysis and the acquisition of conclusion.